Avaliação de Diferentes Compósitos na Resistência à Fratura de Núcleos de Preenchimento - de Souza Setúbal Destro, Andrey [UNESP]; Uemura, Eduardo Shigueyuki [UNESP]; Yamamoto, Eron Toshio Colauto [UNESP] (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2010)
Objective: To evaluate and compare the fracture strength of different composite resins used for core buildup. Method: Thirty-six bovine teeth were decoronated at the cervical third to standardize the length of specimens at 20 mm. Under constant irrigation, the canals were prepared with #5 Largo drills corresponding to the size and diameter of #3 Reforpost fiberglass post. The posts were cemented with Enforce resin sealer, being 16 mm inside the root canal and 4 mm outside the root canal, and the material was light-activated for 30 seconds at each side. The specimens were divided into 3 groups (n=12), in which cores (4 mm diameter and 5 mm high) were prepared from a prefabricated standard with three types of composite resins: Group 1: Z100 (3M), Group 2: Z250 (3M) and Group 3: P60 (3M). The specimens were fixed in a cylindrical device with an adaptor at 45o inclination. This device was adapted to a universal testing machine (EMIC) to simulate the force until fracture of the specimen. Data were subjected to ANOVA (p<0.05). Results: The Z250 resin cores presented the highest mean fracture strength (45.453 kgf), while the mean fracture strengths in Group 1 and Group 3 were 38.014 and 39.506 kgf, respectively. P60 caused the largest number of root fractures. Conclusion: Considering the characteristics and properties of the tested resins, Z250 appears as the most indicated for core buildup.
Evaluation of the fracture strength of different composites used for core buildup
Keywords: Composite resins; Fratura de dente; Material resistance; Resinas compostas; Resistência de materiais; Tooth fractures